2018
DOI: 10.14245/ns.1836004.022
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Transverse Foramen in the Subaxial Cervical Spine in Korean Patients With Degenerative Changes: An Anatomical Note

Abstract: Background/AimsThe purpose of this study was to provide anatomical data on the dimensions and location of the subaxial transverse foramen (TF) in relation to surgical landmarks routinely used during anterior cervical procedures. MethodsA total of 116 patients who underwent preoperative computed tomography (CT) evaluations for degenerative cervical disease were enrolled. Axial and coronal CT images of the cervical vertebrae from C3 to C6 were analyzed to measure interforaminal distance, the TF distance from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Our study provides preliminary data on the spatial relationship between the transverse foramina and the size of the arteries within extant human cervical vertebrae. As in the study by Cagnie et al ( 2005 ), we did find that the size of the foramina increased from C3 to C6, which is also confirmed, to a lesser extent, by Malla et al ( 2018 ). However, contrary to previous studies (Sanelli et al, 2002 ; Cagnie et al, 2005 ; Kim et al, 2012 ; Kotil & Kilincer, 2014 ; Abd El Gawad et al, 2019 ; but see Sangari et al, 2015 about the size of the foramina), our analysis did not show any significant asymmetries between right and left transverse foramina or arteries.…”
Section: Discussionsupporting
confidence: 91%
“…Our study provides preliminary data on the spatial relationship between the transverse foramina and the size of the arteries within extant human cervical vertebrae. As in the study by Cagnie et al ( 2005 ), we did find that the size of the foramina increased from C3 to C6, which is also confirmed, to a lesser extent, by Malla et al ( 2018 ). However, contrary to previous studies (Sanelli et al, 2002 ; Cagnie et al, 2005 ; Kim et al, 2012 ; Kotil & Kilincer, 2014 ; Abd El Gawad et al, 2019 ; but see Sangari et al, 2015 about the size of the foramina), our analysis did not show any significant asymmetries between right and left transverse foramina or arteries.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the recent study showed significantly higher AP diameters of C6-7 and T diameter of only C7 in male, indicating that such parameters could be used to be very helpful in forensic identification of complete cervical vertebral FT remains. These findings were similar to those of previous reports in Korean (Malla et al, 2018) and Spanish populations (Quiles-Guiñau et al, 2017) but differed in that the C5 T diameter in females in our study was significantly longer than in the males. Consideration of lateral size differences may help prevent left vertebral neurovascular damage during spinal surgery.…”
Section: Discussionsupporting
confidence: 91%
“…FT variation is clinically significant to radiologists and surgeons planning posterior operations at the lower cervical spine (C3-C7). The morphometry (such as type and diameter) and rates of variance of FT have been found to differ by population, with previous studies being conducted in Israel, Japan, China, India, Italy, Turkey, the US, Greece, Spain, Chile, South Africa, and Korea (Taitz et al 1978;Kimura et al, 1985;Sangari et al, 2015;Zibis et al, 2016;Quiles-Guiñau et al, 2017;Guerra et al, 2017;Abdul et al, 2018;Malla et al, 2018;Gupta & Agarwal, 2019). Ours was the first study to report the incidence of variance and morphometric features of the lower cervical spine FT in a Thai population.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Additionally, these variations are important for surgeons and radiologists to consider prior to surgery on the posterior upper cervical spine [13]. The morphometric alterations of FT diameters have been documented in many populations including Chilean [6], Kenyan [8], Greek [4], Indian [7,14], American [15], Turkish [16], Japanese [17], Chinese [17], and Korean [18].…”
Section: Discussionmentioning
confidence: 99%